The effect of trade liberalization on inter-industry wage difference in Indonesia's manufacturing sector - Watekhi Watekhi; Nachrowi D. Nachrowi (Cogent Economics & Finance, 2020)
This study analyzes the effect of trade liberalization on wage inequality through industry wage premiums in Indonesia's manufacturing sector between 2000 and 2015, a period marked by low import tariffs. The study was undertaken by adopting a two-stage estimation approach. Using the national labor force survey dataset from Sakernas (Survei Angkatan Kerja Nasional-Indonesia Labor Force Survey), first, the study estimates industry wage premiums conditional on individual worker characteristics. In the second stage, the data are pooled across industries over time, then regressed on import tariff of final goods as a measure of trade liberalization, controlling for market concentration. The study finds a negative effect of import tariffs on industry wage premiums, implying that industry wage premiums decreased by more in sectors facing a larger tariff hike, and, vice versa, industry wage premiums increased by more in sectors experiencing larger tariff cuts. This suggests that trade liberalization contributes to wider wage inequality through inter-industry wage difference. Therefore, a more selective measure should be taken in implementing trade liberalization by opening wider access for superior commodities and protecting less-competitive commodities with high domestic demand.
Keywords: F14; F16; J31; 330; inter-industry wage difference; trade liberalization; wage inequality